Analysis of an Integrated QEEG-Neurofeedback System Utilizing Active Stimuli for Non-Pharmacological Intervention in Enhancing Neurobehavioral Function - Mahatidana, Pradipta; Musridharta, Eka; Basari (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
Quantitative Electroencephalogram (QEEG) and Neurofeedback (NF) are employed in the diagnosis and treatment of neurobehavioral deficits associated with various clinical conditions. These approaches enable the exploration of EEG usage within the context of neurobehavioral electrophysiology. This study aims to elucidate the fundamental evidence supporting NF and to outline strategies for its further development and application in ameliorating neurobehavioral deficits. Numerous research studies have demonstrated the efficacy of NF in enhancing neurobehavioral functions, including attention, language, memory, visuospatial abilities, and executive function. This study intends to develop an NF system that includes the establishment of a robust approach to QEEG transformation and database. The closed-loop QEEG-NF system under development incorporates active visual and auditory stimuli that leverage stochastic phenomena. The efficacy of the QEEG NF treatment was confirmed with a statistically significant increase in alpha brain wave percentages post-treatment (p = 0.018), indicating that the system effectively enhances alpha brain wave production.